Russian Energy Security and Foreign Policy. - Dellecker, Adrian (Taylor & Francis, 2011)
This book provides an original and thoroughly academic analysis of the link between Russian energy and foreign policies in Eurasia, as well as offering an interpretation of Russia's coherence on the international stage.